PERKEMBANGAN ALIRAN PENCAK SILAT TRADISIONAL BAKTI JANG PAT PETULAI DAERAH TUNGGANG ULAU DUES KABUPATEN LEBONG - Helvi Darsi; Muhammad Supriyadi (JURNAL STAMINA, 2018)
The research begins with the fact that the Bakti Jang Pat Traditional Pencak Silat Petition should have developed and cultivated has begun to be abandoned and its development has diminished, it is feared that this Pencak Silat will disappear so developments for inventory must be maintained so that it does not disappear. This study aims to get an overview of the Bakti Traditional Pencak Silat. This type of research is qualitative, the data is taken through observation and interviews using snowball techniques through a key informant, namely Tua Silat Bakti, from the informant that other informants developed so that all data needed is met, then analyzed using words that can be arranged in text expanded or analyzed from data taken from the field and then described in narrative form. The results of the study are as follows: according to information on traditional pencak silat this comes from the filial word that first developed it was the grandmother of Monyang, Pencak Silat It developed rapidly in 1965 to 1990, and the people of Runggang began to learn less about Jakti Pat Petulai Traditional Pencak Silat since 1987. The main form of the Pencak Silat movement will be seen in the speed and accuracy of the attack and the attack of the sword (sword), elakan and attack piseu (knife), as well as accuracy and attack with empty tangents (empty handed).